Model Komunikasi Pemasaran Bisnis Jasa - Zakaria Lantang Sukirno (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2017)
Abstract Marketing communication is one of the tools of service business which base onhospitality. From practical and tacktical aspec integrated maketing communicationactivities is marketing communication mix “7P”; advertising, direct marketing,digital marketing/internet, sales promotion, public relations and personal selling.Integrated marketing communication for service business must adaptation to social,culture, economic situations and market targeting. The core of succesful of servicebusiness are uniqueness, quality and excellent service of the product throughinteraktif marketing. Key Word: marketing communication, service business